A biodegradable blister box natural resin composite material and preparation method thereof

Through the blending of natural plant resin and polylactic acid and the coordination of other components, a degradable respirator box natural resin composite material with good biodegradability, mechanical properties and processing properties was prepared, solving the problems of high cost and insufficient performance of existing biodegradable plastics, and achieving environmentally friendly and economical packaging materials.

CN119735959APending Publication Date: 2025-04-01SUZHOU ULTRAPACK MEDICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411887656.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing biodegradable plastics have high cost, complex production process, limited degradation conditions, and insufficient mechanical properties and molding properties, which limit their application in the field of blister boxes.

Method used

The blending of natural plant resin and polylactic acid is used to combine emulsifier composites, calcium carbonate, talc powder and other components, and a degradable absorbent box natural resin composite material is formed through specific preparation methods and process flows.

Benefits of technology

It has achieved improvements in biodegradability, mechanical properties and processing properties, reduced production costs, improved market competitiveness, and reduced environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735959A_ABST
    Figure CN119735959A_ABST
Patent Text Reader

Abstract

The invention discloses a natural resin composite material for a degradable blister box and a preparation method thereof. The composite material comprises, by weight, 20 to 25 parts of natural plant resin, 8 to 10 parts of polylactic acid, 5 to 7 parts of an emulsifier compound, 1 to 2 parts of a dissolving agent, 5 to 8 parts of calcium carbonate, 3 to 5 parts of talcum powder, 1 to 2 parts of an antioxidant, 1 to 3 parts of a lubricant, 1 to 5 parts of a catalyst, 1.2 parts of a coupling agent, 1 to 5 parts of a 3% sodium bicarbonate aqueous solution and 30 to 35 parts of an ethyl acetate solvent. The environmental pollution is reduced by compounding the natural plant resin with biodegradable materials such as PLA; the composite material has good mechanical properties due to the optimization of reasonable component proportions and chemical action mechanisms; the composite material exhibits good fluidity and formability during processing by using the emulsifier compound and the coupling agent; the production cost is reduced to a certain extent by utilizing low-cost raw materials and fillers and an optimized preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of research and development of environmentally friendly packaging materials, and in particular to a degradable blister box natural resin composite material and a preparation method thereof. Background Art

[0002] Traditional blister boxes are usually made of plastic materials such as polyethylene and polypropylene, which are difficult to degrade and cause environmental pollution.

[0003] Although biodegradable plastics exist on the market, they are expensive, have a complex production process, and have limited degradation conditions. In addition, the degradable materials in the prior art often have deficiencies in mechanical properties and molding properties, which limits their application in the field of blister boxes. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems existing in the existing biodegradable plastics, the present invention is proposed.

[0006] Therefore, the technical problem solved by the present invention is to solve the problems that existing biodegradable plastics have high costs, complex production processes, limited degradation conditions, and insufficient mechanical properties and molding properties.

[0007] To solve the above technical problems, the present invention provides the following technical solutions: a biodegradable blister box natural resin composite material, comprising the following components by weight: 20-25 parts of natural plant resin, 8-10 parts of polylactic acid, 5-7 parts of emulsifier compound, 1-2 parts of solvent, 5-8 parts of calcium carbonate, 3-5 parts of talc, 1-2 parts of antioxidant, 1-3 parts of lubricant, 1-5 parts of catalyst, 1.2 parts of coupling agent, 1-5 parts of 3% sodium bicarbonate aqueous solution, and 30-35 parts of ethyl acetate solvent.

[0008] As a preferred solution of the natural resin composite material for the degradable blister box of the present invention, the emulsifier compound comprises a polyethylene glycol type nonionic surfactant and an anionic surfactant mixed in a ratio of 1:3.

[0009] As a preferred embodiment of the biodegradable blister box natural resin composite material of the present invention, the solvent is one of formic acid, acetonitrile, acetone or butanone or a mixture of any two of them in a ratio of 1:2.

[0010] As a preferred embodiment of the biodegradable blister box natural resin composite material of the present invention, the antioxidant is a compound mixture of 2,6-di-tert-butyl-p-cresol and diphenyl-p-phenylenediamine at a ratio of 1:1.1.

[0011] As a preferred solution of the biodegradable blister box natural resin composite material of the present invention, the catalyst is a mixture of glutathione and polyvinyl pyrrolidone in a mass ratio of 2.7:1.

[0012] As a preferred solution of the biodegradable blister box natural resin composite material of the present invention, the coupling agent is vinyl triethoxy silane.

[0013] In order to solve the above technical problems, the present invention also provides the following technical solutions: a method for preparing a natural resin composite material for a degradable blister box, which is prepared by the following steps: S1: quantitatively weighing, weighing all the above raw materials according to the above component ratio; S2: preheating the reactor to 80°C, maintaining the temperature in the range of 78-82°C, adding natural plant resin, polylactic acid and emulsifier compound, slowly dripping the solvent at a rate of 0.5 mol / min, and continuously controlling the temperature after the solvent is completely dripped, and stirring the reaction for 30 minutes; S3: adding calcium carbonate and talcum powder during the stirring process, stirring to control the viscosity , after the viscosity reaches the standard, antioxidant, lubricant and coupling agent are added in sequence; S4: cool to 50°C, add ethyl acetate solvent, maintain the temperature and stir for 1h, then configure a reflux device and reflux for 1h; S5: remove the reflux device, take out the mixture from the reactor, add catalyst and 3% sodium bicarbonate aqueous solution, pour the reactants into the electrode catalytic system with an external power supply, electrode catalyze for 12h, re-measure the viscosity, and filter out the adhesive when the viscosity reaches the standard; S6: hot pressing: put the mixture in S5 into a hot press for hot pressing to form a composite material sheet; S7: cooling: cool the hot pressed sheet to room temperature and wait for vacuum forming.

[0014] As a preferred embodiment of the method for preparing the biodegradable blister box natural resin composite material of the present invention, wherein: the viscosity of S3 is 200-500mm 2 / s, the qualification standard is met.

[0015] As a preferred solution of the method for preparing the natural resin composite material for the degradable blister box of the present invention, wherein: the electrode catalytic system is externally connected to a 24v±5V power supply.

[0016] As a preferred embodiment of the method for preparing the biodegradable blister box natural resin composite material of the present invention, the viscosity of S5 is 800-1200 mm 2 / s, the qualification standard is met.

[0017] The present invention provides a biodegradable blister box natural resin composite material and a preparation method thereof:

[0018] 1. Blending of natural plant resin and polylactic acid (PLA): Both natural plant resin and PLA are high molecular polymers, which can be combined together by physical blending. PLA is a bio-based polymer made from renewable resources (such as corn or sugar cane), and its main chain contains ester bonds, which can be decomposed by microorganisms under certain conditions, thereby achieving biodegradation. The components in natural plant resin form hydrogen bonds or other types of intermolecular forces with PLA, enhancing the compatibility and mechanical properties of the blend.

[0019] 2. Stabilizing effect of emulsifier compound: Nonionic and anionic surfactants in emulsifier compound can reduce interfacial tension and promote uniform dispersion of different components. This stabilizing effect helps to form a uniform composite material and improve its mechanical strength and processing performance.

[0020] 3. Combination of fillers and resins: Fillers such as calcium carbonate and talcum powder play a reinforcing role in composite materials. The addition of fillers can improve the rigidity of the material and reduce the cost. In the preparation process of composite materials, coupling agents (such as vinyl triethoxysilane) can be used to improve the interface bonding between fillers and resins and improve the interface adhesion.

[0021] 4. Synergistic effect of catalysts and antioxidants: Catalysts can accelerate polymerization reactions and promote the formation of a stable network structure of materials, while antioxidants can prevent or slow down the oxidation process of materials during production and service life, thereby extending the service life of materials.

[0022] 5. The role of solvent and sodium bicarbonate aqueous solution: Ethyl acetate solvent is used to dissolve certain components in the preparation process to help the mixing and polymerization process. Sodium bicarbonate aqueous solution is used to adjust the pH value of the reaction environment and assist the electrode catalytic reaction, affecting the rate and direction of the chemical reaction.

[0023] Technical effects:

[0024] Biodegradability: By using biodegradable materials such as natural plant resins and PLA, composite materials can be decomposed by microorganisms under natural conditions, reducing environmental pollution.

[0025] Mechanical properties: Reasonable component ratio and optimization of chemical action mechanism make the composite material have good mechanical properties, including impact resistance, rigidity and flexibility, which is suitable for packaging materials such as blister boxes.

[0026] Processing performance: Through the use of emulsifier compound and coupling agent, the composite material shows good fluidity and formability during processing, which is conducive to large-scale production.

[0027] Economical: The use of low-cost raw materials and fillers, as well as optimized preparation processes, can reduce production costs and improve market competitiveness to a certain extent.

[0028] Environmental friendliness: The environmental friendliness of composite materials is not only reflected in their biodegradability, but also in the use of renewable resources as raw materials, reducing dependence on fossil fuels. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0030] Figure 1 The present invention is a flow chart of a method for preparing a natural resin composite material for a degradable blister box. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.

[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] The biodegradable plastics on the market have high costs, complex production processes, and limited degradation conditions. They also often have deficiencies in mechanical and molding properties, which limits their application in the blister box field.

[0035] Therefore, the present invention provides a biodegradable blister box natural resin composite material and a preparation method thereof. Please refer to the following embodiments for details:

[0036] Example 1

[0037] The present embodiment provides a biodegradable blister box natural resin composite material, which includes the following components by weight: 20 parts of natural plant resin, 8 parts of polylactic acid, 5 parts of emulsifier compound, 1 part of solvent, 5 parts of calcium carbonate, 3 parts of talcum powder, 1 part of antioxidant, 1 part of lubricant, 1 part of catalyst, 1.2 parts of coupling agent, 1 part of 3% sodium bicarbonate aqueous solution, and 30 parts of ethyl acetate solvent.

[0038] The emulsifier compound includes a polyethylene glycol type nonionic surfactant (such as polyoxyethylene stearate) and an anionic surfactant (such as sodium lauryl sulfate) mixed in a ratio of 1:3.

[0039] The solvent is one of formic acid, acetonitrile, acetone or butanone or a mixture of any two of them in a ratio of 1:2.

[0040] The antioxidant is 2,6-di-tert-butyl-p-cresol and diphenyl-p-phenylenediamine mixed in a ratio of 1:1.1.

[0041] The catalyst is a mixture of glutathione and polyvinyl pyrrolidone in a mass ratio of 2.7:1.

[0042] Wherein, the coupling agent is vinyltriethoxysilane.

[0043] For additional information, see Figure 1 The present invention also provides a method for preparing a biodegradable blister box natural resin composite material, which is prepared by the following steps:

[0044] S1: quantitatively weigh all the above raw materials according to the above component ratio;

[0045] S2: Preheat the reactor to 80°C, maintain the temperature at 78-82°C, add natural plant resin, polylactic acid and emulsifier compound, slowly drop the solvent at a rate of 0.5 mol / min, and continue to control the temperature after the solvent is completely added, and stir the reaction for 30 minutes;

[0046] S3: Add calcium carbonate and talcum powder during stirring, stir to control viscosity, and add antioxidant, lubricant and coupling agent in sequence after the viscosity reaches the standard;

[0047] S4: Cool down to 50°C, add ethyl acetate solvent, stir at this temperature for 1 hour, then install a reflux device and reflux for 1 hour;

[0048] S5: Remove the reflux device, take out the mixture from the reactor, add the catalyst and 3% sodium bicarbonate aqueous solution, pour the reactants into the electrode catalytic system and connect the external power supply, perform electrode catalysis for 12 hours, re-measure the viscosity, and filter out the adhesive when the viscosity reaches the standard;

[0049] S6: hot pressing: placing the mixture in S5 into a hot press for hot pressing to form a composite material sheet;

[0050] S7: Cooling: Cool the hot-pressed sheet to room temperature and wait for blister forming.

[0051] Specifically, the viscosity of S3 is 200-500mm 2 / s, the qualification standard is met.

[0052] Specifically, an external 24v±5V power supply is connected to the electrode catalytic system.

[0053] Specifically, the viscosity of S5 is 800~1200mm 2 / s, the qualification standard is met.

[0054] Example 2

[0055] The present embodiment provides a natural resin composite material for a degradable blister box, which includes the following components by weight: 25 parts of natural plant resin, 10 parts of polylactic acid, 7 parts of an emulsifier compound, 2 parts of a solvent, 8 parts of calcium carbonate, 5 parts of talc, 2 parts of an antioxidant, 3 parts of a lubricant, 5 parts of a catalyst, 1.2 parts of a coupling agent, 5 parts of a 3% sodium bicarbonate aqueous solution, and 35 parts of an ethyl acetate solvent.

[0056] The emulsifier compound includes a polyethylene glycol type nonionic surfactant (such as polyoxyethylene stearate) and an anionic surfactant (such as sodium lauryl sulfate) mixed in a ratio of 1:3.

[0057] The solvent is one of formic acid, acetonitrile, acetone or butanone or a mixture of any two of them in a ratio of 1:2.

[0058] The antioxidant is 2,6-di-tert-butyl-p-cresol and diphenyl-p-phenylenediamine mixed in a ratio of 1:1.1.

[0059] The catalyst is a mixture of glutathione and polyvinyl pyrrolidone in a mass ratio of 2.7:1.

[0060] Wherein, the coupling agent is vinyltriethoxysilane.

[0061] For additional information, see Figure 1 The present invention also provides a method for preparing a biodegradable blister box natural resin composite material, which is prepared by the following steps:

[0062] S1: quantitatively weigh all the above raw materials according to the above component ratio;

[0063] S2: Preheat the reactor to 80°C, maintain the temperature at 78-82°C, add natural plant resin, polylactic acid and emulsifier compound, slowly drop the solvent at a rate of 0.5 mol / min, and continue to control the temperature after the solvent is completely added, and stir the reaction for 30 minutes;

[0064] S3: Add calcium carbonate and talcum powder during stirring, stir to control viscosity, and add antioxidant, lubricant and coupling agent in sequence after the viscosity reaches the standard;

[0065] S4: Cool down to 50°C, add ethyl acetate solvent, stir at this temperature for 1 hour, then install a reflux device and reflux for 1 hour;

[0066] S5: Remove the reflux device, take out the mixture from the reactor, add the catalyst and 3% sodium bicarbonate aqueous solution, pour the reactants into the electrode catalytic system and connect the external power supply, perform electrode catalysis for 12 hours, re-measure the viscosity, and filter out the adhesive when the viscosity reaches the standard;

[0067] S6: hot pressing: placing the mixture in S5 into a hot press for hot pressing to form a composite material sheet;

[0068] S7: Cooling: Cool the hot-pressed sheet to room temperature and wait for blister forming.

[0069] Specifically, the viscosity of S3 is 200-500mm 2 / s, the qualification standard is met.

[0070] Specifically, an external 24v±5V power supply is connected to the electrode catalytic system.

[0071] Specifically, the viscosity of S5 is 800~1200mm 2 / s, the qualification standard is met.

[0072] Example 3

[0073] The present embodiment provides a biodegradable blister box natural resin composite material, which includes the following components by weight: 23 parts of natural plant resin, 9 parts of polylactic acid, 6 parts of emulsifier compound, 2 parts of solvent, 6 parts of calcium carbonate, 4 parts of talcum powder, 1 part of antioxidant, 2 parts of lubricant, 3 parts of catalyst, 1.2 parts of coupling agent, 3 parts of 3% sodium bicarbonate aqueous solution, and 33 parts of ethyl acetate solvent.

[0074] The emulsifier compound includes a polyethylene glycol type nonionic surfactant (such as polyoxyethylene stearate) and an anionic surfactant (such as sodium lauryl sulfate) mixed in a ratio of 1:3.

[0075] The solvent is one of formic acid, acetonitrile, acetone or butanone or a mixture of any two of them in a ratio of 1:2.

[0076] The antioxidant is 2,6-di-tert-butyl-p-cresol and diphenyl-p-phenylenediamine mixed in a ratio of 1:1.1.

[0077] The catalyst is a mixture of glutathione and polyvinyl pyrrolidone in a mass ratio of 2.7:1.

[0078] Wherein, the coupling agent is vinyltriethoxysilane.

[0079] For additional information, see Figure 1 The present invention also provides a method for preparing a biodegradable blister box natural resin composite material, which is prepared by the following steps:

[0080] S1: quantitatively weigh all the above raw materials according to the above component ratio;

[0081] S2: Preheat the reactor to 80°C, maintain the temperature at 78-82°C, add natural plant resin, polylactic acid and emulsifier compound, slowly drop the solvent at a rate of 0.5 mol / min, and continue to control the temperature after the solvent is completely added, and stir the reaction for 30 minutes;

[0082] S3: Add calcium carbonate and talcum powder during stirring, stir to control viscosity, and add antioxidant, lubricant and coupling agent in sequence after the viscosity reaches the standard;

[0083] S4: Cool down to 50°C, add ethyl acetate solvent, stir at this temperature for 1 hour, then install a reflux device and reflux for 1 hour;

[0084] S5: Remove the reflux device, take out the mixture from the reactor, add the catalyst and 3% sodium bicarbonate aqueous solution, pour the reactants into the electrode catalytic system and connect the external power supply, perform electrode catalysis for 12 hours, re-measure the viscosity, and filter out the adhesive when the viscosity reaches the standard;

[0085] S6: hot pressing: placing the mixture in S5 into a hot press for hot pressing to form a composite material sheet;

[0086] S7: Cooling: Cool the hot-pressed sheet to room temperature and wait for blister forming.

[0087] Specifically, the viscosity of S3 is 200-500mm 2 / s, the qualification standard is met.

[0088] Specifically, an external 24v±5V power supply is connected to the electrode catalytic system.

[0089] Specifically, the viscosity of S5 is 800~1200mm 2 / s, the qualification standard is met.

[0090] Example 4

[0091] The present embodiment provides a biodegradable blister box natural resin composite material, which includes the following components by weight: 21 parts of natural plant resin, 8 parts of polylactic acid, 5 parts of emulsifier compound, 1 part of solvent, 7 parts of calcium carbonate, 3 parts of talcum powder, 1 part of antioxidant, 1 part of lubricant, 4 parts of catalyst, 1.2 parts of coupling agent, 4 parts of 3% sodium bicarbonate aqueous solution, and 31 parts of ethyl acetate solvent.

[0092] The emulsifier compound includes a polyethylene glycol type nonionic surfactant (such as polyoxyethylene stearate) and an anionic surfactant (such as sodium lauryl sulfate) mixed in a ratio of 1:3.

[0093] The solvent is one of formic acid, acetonitrile, acetone or butanone or a mixture of any two of them in a ratio of 1:2.

[0094] The antioxidant is 2,6-di-tert-butyl-p-cresol and diphenyl-p-phenylenediamine mixed in a ratio of 1:1.1.

[0095] The catalyst is a mixture of glutathione and polyvinyl pyrrolidone in a mass ratio of 2.7:1.

[0096] Wherein, the coupling agent is vinyltriethoxysilane.

[0097] For additional information, see Figure 1 The present invention also provides a method for preparing a biodegradable blister box natural resin composite material, which is prepared by the following steps:

[0098] S1: quantitatively weigh all the above raw materials according to the above component ratio;

[0099] S2: Preheat the reactor to 80°C, maintain the temperature at 78-82°C, add natural plant resin, polylactic acid and emulsifier compound, slowly drop the solvent at a rate of 0.5 mol / min, and continue to control the temperature after the solvent is completely added, and stir the reaction for 30 minutes;

[0100] S3: Add calcium carbonate and talcum powder during stirring, stir to control viscosity, and add antioxidant, lubricant and coupling agent in sequence after the viscosity reaches the standard;

[0101] S4: Cool down to 50°C, add ethyl acetate solvent, stir at this temperature for 1 hour, then install a reflux device and reflux for 1 hour;

[0102] S5: Remove the reflux device, take out the mixture from the reactor, add the catalyst and 3% sodium bicarbonate aqueous solution, pour the reactants into the electrode catalytic system and connect the external power supply, perform electrode catalysis for 12 hours, re-measure the viscosity, and filter out the adhesive when the viscosity reaches the standard;

[0103] S6: hot pressing: placing the mixture in S5 into a hot press for hot pressing to form a composite material sheet;

[0104] S7: Cooling: Cool the hot-pressed sheet to room temperature and wait for blister forming.

[0105] Specifically, the viscosity of S3 is 200-500mm 2 / s, the qualification standard is met.

[0106] Specifically, an external 24v±5V power supply is connected to the electrode catalytic system.

[0107] Specifically, the viscosity of S5 is 800~1200mm 2 / s, the qualification standard is met.

[0108] Example 5

[0109] The present embodiment provides a natural resin composite material for a degradable blister box, which includes the following components by weight: 24 parts of natural plant resin, 10 parts of polylactic acid, 7 parts of an emulsifier compound, 2 parts of a solvent, 8 parts of calcium carbonate, 3 parts of talcum powder, 2 parts of an antioxidant, 1 part of a lubricant, 4 parts of a catalyst, 1.2 parts of a coupling agent, 2 parts of a 3% sodium bicarbonate aqueous solution, and 32 parts of an ethyl acetate solvent.

[0110] The emulsifier compound includes a polyethylene glycol type nonionic surfactant (such as polyoxyethylene stearate) and an anionic surfactant (such as sodium lauryl sulfate) mixed in a ratio of 1:3.

[0111] The solvent is one of formic acid, acetonitrile, acetone or butanone or a mixture of any two of them in a ratio of 1:2.

[0112] The antioxidant is 2,6-di-tert-butyl-p-cresol and diphenyl-p-phenylenediamine mixed in a ratio of 1:1.1.

[0113] The catalyst is a mixture of glutathione and polyvinyl pyrrolidone in a mass ratio of 2.7:1.

[0114] Wherein, the coupling agent is vinyltriethoxysilane.

[0115] For additional information, see Figure 1 The present invention also provides a method for preparing a biodegradable blister box natural resin composite material, which is prepared by the following steps:

[0116] S1: quantitatively weigh all the above raw materials according to the above component ratio;

[0117] S2: Preheat the reactor to 80°C, maintain the temperature at 78-82°C, add natural plant resin, polylactic acid and emulsifier compound, slowly drop the solvent at a rate of 0.5 mol / min, and continue to control the temperature after the solvent is completely added, and stir the reaction for 30 minutes;

[0118] S3: Add calcium carbonate and talcum powder during stirring, stir to control viscosity, and add antioxidant, lubricant and coupling agent in sequence after the viscosity reaches the standard;

[0119] S4: Cool down to 50°C, add ethyl acetate solvent, stir at this temperature for 1 hour, then install a reflux device and reflux for 1 hour;

[0120] S5: Remove the reflux device, take out the mixture from the reactor, add the catalyst and 3% sodium bicarbonate aqueous solution, pour the reactants into the electrode catalytic system and connect the external power supply, perform electrode catalysis for 12 hours, re-measure the viscosity, and filter out the adhesive when the viscosity reaches the standard;

[0121] S6: hot pressing: placing the mixture in S5 into a hot press for hot pressing to form a composite material sheet;

[0122] S7: Cooling: Cool the hot-pressed sheet to room temperature and wait for blister forming.

[0123] Specifically, the viscosity of S3 is 200-500mm 2 / s, the qualification standard is met.

[0124] Specifically, an external 24v±5V power supply is connected to the electrode catalytic system.

[0125] Specifically, the viscosity of S5 is 800~1200mm 2 / s, the qualification standard is met.

[0126] Test verification process:

[0127] Raw material preparation: Various raw materials are accurately weighed according to the ratio given in the invention scheme, including natural plant resin, polylactic acid, emulsifier compound, solvent, calcium carbonate, talcum powder, antioxidant, lubricant, catalyst, coupling agent, 3% sodium bicarbonate aqueous solution and ethyl acetate solvent.

[0128] Mixing and polymerization: The above raw materials are mixed uniformly in a reaction kettle, a catalyst and a 3% sodium bicarbonate aqueous solution are added, and then a polymerization reaction is carried out in an electrode catalytic system connected to an external power source, during which the viscosity of the reactants is measured and adjusted.

[0129] Hot pressing: The mixture after polymerization is placed in a press for hot pressing to form a composite material sheet.

[0130] Cooling and testing: The hot-pressed sheets are cooled to room temperature and various performance tests are performed on the composite materials, including biodegradability, mechanical properties and processing properties.

[0131] Data analysis: Record and analyze the data of each example to evaluate the technical effect of the composite material.

[0132] Technical certification form:

[0133]

[0134] Biodegradability: The biodegradation rate of a material under certain conditions is determined by specific test methods (such as ASTM D6400).

[0135] Tensile strength, elastic modulus and elongation at break: Standard mechanical property tests are used to evaluate the performance of materials during tension.

[0136] Processing fluidity: The melt flow index (MFI) is measured to evaluate the fluidity of the material during processing. The lower the value, the better the fluidity.

[0137] The present invention provides a biodegradable blister box natural resin composite material and a preparation method thereof:

[0138] 1. Blending of natural plant resin and polylactic acid (PLA): Both natural plant resin and PLA are high molecular polymers, which can be combined together by physical blending. PLA is a bio-based polymer made from renewable resources (such as corn or sugar cane), and its main chain contains ester bonds, which can be decomposed by microorganisms under certain conditions, thereby achieving biodegradation. The components in natural plant resin form hydrogen bonds or other types of intermolecular forces with PLA, enhancing the compatibility and mechanical properties of the blend.

[0139] 2. Stabilizing effect of emulsifier compound: Nonionic and anionic surfactants in emulsifier compound can reduce interfacial tension and promote uniform dispersion of different components. This stabilizing effect helps to form a uniform composite material and improve its mechanical strength and processing performance.

[0140] 3. Combination of fillers and resins: Fillers such as calcium carbonate and talcum powder play a reinforcing role in composite materials. The addition of fillers can improve the rigidity of the material and reduce the cost. In the preparation process of composite materials, coupling agents (such as vinyl triethoxysilane) can be used to improve the interface bonding between fillers and resins and improve the interface adhesion.

[0141] 4. Synergistic effect of catalysts and antioxidants: Catalysts can accelerate polymerization reactions and promote the formation of a stable network structure of materials, while antioxidants can prevent or slow down the oxidation process of materials during production and service life, thereby extending the service life of materials.

[0142] 5. The role of solvent and sodium bicarbonate aqueous solution: Ethyl acetate solvent is used to dissolve certain components in the preparation process to help the mixing and polymerization process. Sodium bicarbonate aqueous solution is used to adjust the pH value of the reaction environment and assist the electrode catalytic reaction, affecting the rate and direction of the chemical reaction.

[0143] Technical effects:

[0144] Biodegradability: By using biodegradable materials such as natural plant resins and PLA, composite materials can be decomposed by microorganisms under natural conditions, reducing environmental pollution.

[0145] Mechanical properties: Reasonable component ratio and optimization of chemical action mechanism make the composite material have good mechanical properties, including impact resistance, rigidity and flexibility, which is suitable for packaging materials such as blister boxes.

[0146] Processing performance: Through the use of emulsifier compound and coupling agent, the composite material shows good fluidity and formability during processing, which is conducive to large-scale production.

[0147] Economical: The use of low-cost raw materials and fillers, as well as optimized preparation processes, can reduce production costs and improve market competitiveness to a certain extent.

[0148] Environmental friendliness: The environmental friendliness of composite materials is not only reflected in their biodegradability, but also in the use of renewable resources as raw materials, reducing dependence on fossil fuels.

[0149] Importantly, it should be noted that the construction and arrangement of the present application shown in a plurality of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible (e.g., the size, scale, structure, shape and proportion of various elements, and parameter values ​​(e.g., temperature, pressure, etc.), installation arrangement, use of materials, color, directional changes, etc.) without substantially departing from the novel teachings and advantages of the subject matter described in the application. For example, the element shown as integrally formed can be composed of multiple parts or elements, the position of the element can be inverted or otherwise changed, and the nature or number or position of the discrete element can be changed or changed. Therefore, all such modifications are intended to be included in the scope of the present invention. The order or sequence of any process or method steps can be changed or reordered according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure of performing the function described herein, and is not only structurally equivalent but also equivalent structure. Without departing from the scope of the present invention, other replacements, modifications, changes and omissions can be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the invention is not limited to a specific embodiment, but extends to numerous modifications still falling within the scope of the appended claims.

[0150] Additionally, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment (ie, those features that are not relevant to the best mode presently contemplated for carrying out the invention or those that are not relevant to implementing the invention) may not be described.

[0151] It will be appreciated that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but will be a routine task of design, fabrication, and production for those of ordinary skill having the benefit of this disclosure without undue experimentation.

[0152] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the invention.

Claims

1. A biodegradable blister box natural resin composite material, characterized in that: The invention comprises the following components by weight: 20-25 parts of natural plant resin, 8-10 parts of polylactic acid, 5-7 parts of emulsifier compound, 1-2 parts of solvent, 5-8 parts of calcium carbonate, 3-5 parts of talcum powder, 1-2 parts of antioxidant, 1-3 parts of lubricant, 1-5 parts of catalyst, 1.2 parts of coupling agent, 1-5 parts of 3% sodium bicarbonate aqueous solution and 30-35 parts of ethyl acetate solvent.

2. The biodegradable natural resin composite material for blister box according to claim 1, characterized in that: The emulsifier compound comprises a polyethylene glycol type nonionic surfactant and an anionic surfactant mixed in a ratio of 1:

3.

3. The biodegradable natural resin composite material for blister box according to claim 2, characterized in that: The solvent is one of formic acid, acetonitrile, acetone or butanone, or a mixture of any two of them in a ratio of 1:

2.

4. The biodegradable natural resin composite material for blister box according to claim 3, characterized in that: The antioxidant is a mixture of 2,6-di-tert-butyl-p-cresol and diphenyl-p-phenylenediamine in a ratio of 1:1.

1.

5. The biodegradable natural resin composite material for blister box according to claim 4, characterized in that: The catalyst is a mixture of glutathione and polyvinyl pyrrolidone in a mass ratio of 2.7:

1.

6. The biodegradable natural resin composite material for blister boxes according to claim 5, characterized in that: The coupling agent is vinyltriethoxysilane.

7. A method for preparing a biodegradable blister box natural resin composite material, characterized in that: Prepare by the following steps: S1: quantitatively weigh all the above raw materials according to the above component ratio; S2: Preheat the reactor to 80°C, maintain the temperature at 78-82°C, add natural plant resin, polylactic acid and emulsifier compound, slowly drop the solvent at a rate of 0.5 mol / min, and continue to control the temperature after the solvent is completely added, and stir the reaction for 30 minutes; S3: Add calcium carbonate and talcum powder during stirring, stir to control viscosity, and add antioxidant, lubricant and coupling agent in sequence after the viscosity reaches the standard; S4: Cool down to 50°C, add ethyl acetate solvent, stir at this temperature for 1 hour, then install a reflux device and reflux for 1 hour; S5: Remove the reflux device, take out the mixture from the reactor, add the catalyst and 3% sodium bicarbonate aqueous solution, pour the reactants into the electrode catalytic system and connect the external power supply, perform electrode catalysis for 12 hours, re-measure the viscosity, and filter out the adhesive when the viscosity reaches the standard; S6: hot pressing: placing the mixture in S5 into a hot press for hot pressing to form a composite material sheet; S7: Cooling: Cool the hot-pressed sheet to room temperature and wait for blister forming.

8. The method for preparing the biodegradable blister box natural resin composite material according to claim 7, characterized in that: S3 medium viscosity is 200~500mm 2 / s, the qualification standard is met.

9. The method for preparing the biodegradable blister box natural resin composite material according to claim 8, characterized in that: The electrode catalytic system is externally connected to a 24v±5V power supply.

10. The method for preparing the biodegradable blister box natural resin composite material according to claim 9, characterized in that: S5 medium viscosity is 800~1200mm 2 / s, the qualification standard is met.